Transcription factors Sox5 and Sox6 exert direct and indirect influences on oligodendroglial migration in spinal cord and forebrain. Issue 1 (8th September 2015) - Baroti, Tina; Zimmermann, Yvonne; Schillinger, Anja; Liu, Lina; Lommes, Petra; Wegner, Michael; Stolt, C. Claus
Abstract : Transcription factors of the SoxD protein family have previously been shown to prevent precocious specification and terminal differentiation of oligodendrocyte progenitor cells in the developing spinal cord. Using mice with specific deletion of the SoxD proteins Sox5 and Sox6 in the central nervous system, we now show that SoxD proteins additionally influence migration of oligodendrocyte progenitors in the spinal cord as well as in the forebrain. In mutant mice, emigration of oligodendrocyte progenitors from the ventricular zone and colonization of the mantle zone are significantly delayed probably because of reduced expression of Pdgf receptor alpha and decreased responsiveness toward Pdgf‐A as a main migratory cue. In addition to this direct cell‐autonomous effect on Pdgf receptor alpha expression, SoxD proteins furthermore promote oligodendroglial migration by keeping the cells in an undifferentiated state and preventing a premature loss of their migratory capacity. This indirect effect becomes particularly important during late embryonic and early postnatal phases of oligodendroglial development. Finally, we show that Sox5 and Sox6 cooperate with Sox9 and Sox10 to activate Pdgf receptor alpha expression and thereby maintain oligodendrocyte progenitors in the immature state. This contrasts with their behavior on myelin genes where they antagonize the function of SoxE proteins. It argues that SoxD proteins can function either as repressors or as co‐activators of SoxE proteins thereby modulating their function in a stage‐specific manner. GLIA 2016;64:122–138 Main Points: In addition to specification and differentiation, Sox5/Sox6 regulate migration of OPCs in spinal cord and forebrain in an interplay with SoxE proteins by a direct effect on Pdgfra expression and indirectly by prevention of premature differentiation.